Fourier coefficients of functions from the classes $B$ and $C$. Parseval equality for the class $C$ or for the Fourier-Stieltjes series - Konyushkov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We study restrictions that should be imposed on the numbers sequences $\{α_n\}$ and $\{Β_n\}$ in order to guarantee that the series $\sum olimits_{n = 1}^∞ {a_n } \cos nx$ and $\sum olimits_{n = 1}^∞ {b_n } \sin nx$ do not belong to the classes $B$ or $C$ for any {a n } and {b n } such that $a_n ≥ α_n, b_n ≥ Β_n,\; n = 1, 2$.